Antibacterial Activity of Pineapple Leaf Extract Against the Growth of Ralstonia solanacearum - Aqila, Nisa Aziziyah; Asri, Mahanani Tri (LenteraBio : Berkala Ilmiah Biologi, 2025)
Ralstonia solanacearum attacks plants from the Solanaceae family: potatoes, tomatoes, eggplants and chilies. Chemical control using synthetic pesticides which causes soil pollution and negative environmental impacts. Biology control methods have emerged as a safer and more sustainable alternative use compounds from pineapple leaves (A. comosus L. Merr). This research aims to determine the effect of pineapple leaf extract in inhibiting the growth of R. solanacearum bacteria and to determine the most optimal concentration of pineapple leaf extract in inhibiting the growth of R. solanacearum bacteria. The method used was well diffusion using a Completely Randomized Design (CRD) with extract concentrations used, namely 60%, 80%, 100%, a positive control of 0.01% Streptomycin sulfate and a negative control of 10% DMSO for 5 replications. Data analysis used one-way ANOVA and Duncan’s test. The research results showed that pineapple leaf extract can inhibit the growth of R. solanacearum bacteria. Treatment with a concentration of 100% is the most optimal concentration in inhibiting the growth of R. solanacearum, with inhibition zone diameter of 11.4 ± 0.22 mm. Thus, pineapple leaf extract can contribute to the development of environmentally friendly strategies for managing bacterial wilt disease and reducing dependency on synthetic pesticides.